In Enhancing Preservice Teachers’ Assessment Literacy: Focus on Knowledge Base, Conceptions of Assessment, and Teacher Learning - Päivi Atjonen; Susanna Pöntinen; Sini Kontkanen; Päivi Ruotsalainen (Frontiers in Education, 2022)
Assessment has a critical and time-consuming role in the teaching profession. However, teachers generally possess low levels of assessment knowledge and skills, with their understanding more about the culturally and historically established summative compared to formative assessment. Therefore, developing assessment literacy in preservice teacher education (PsTE) is important. In the present study, a special study module of assessment was designed for PsTE to examine Finnish student teachers’ assessment literacy. Deductive and inductive content analyses of students’ (N = 168) written diaries were conducted applying a conceptual framework of teacher’s assessment literacy in practice (TALiP). Based on the results, the students’ assessment knowledge base and assessment conceptions were promisingly versatile and indicated a rich awareness of the broad nature of assessment. However, the key findings also suggest that assessment is not an easy topic for student teachers to discuss with peers. It can be concluded that even short PsTE assessment courses can enhance student teachers’ views of versatile pedagogical inputs and outputs of assessment.